The Effect of Education Level, Actor Perception, and Accounting Understanding on the Implementation of SAK-EMKM - Muhammad Rizal Faiz; Zulkifli Zulkifli (Research Horizon, 2026)
The implementation of Financial Accounting Standards for Micro, Small, and Medium Enterprises (SAK-EMKM) is crucial for enhancing financial transparency and management, yet the determinants of its successful adoption remain unclear. This study aims to examine the direct and simultaneous influence of business actors’ education level, perceptions, and accounting understanding on the implementation of SAK-EMKM. A quantitative approach was employed, with data collected from culinary MSME owners using structured questionnaires. Multiple regression analysis was conducted to assess the influence of the independent variables on SAK-EMKM implementation. The findings reveal that education level does not significantly affect implementation, while both business actors’ perceptions and accounting understanding have a positive and significant effect, with accounting understanding being the most dominant factor. The study also indicates that these three variables collectively contribute substantially to successful implementation. These results suggest that enhancing practical accounting knowledge and fostering positive perceptions toward financial reporting are more effective strategies than solely focusing on formal education. The study contributes to the literature by highlighting the key determinants of SAK-EMKM adoption in MSMEs and provides practical guidance for policymakers, training institutions, and business support programs aiming to improve financial management practices among culinary MSMEs.